The bookshop of 99 doors - Wright, Jaime Jo (Bethany House Publishers, 2026)
"In 1910, Minnie Tipton finds herself beset by the onslaught of superstitions that envelop the Pennsylvania mansion her father bought. In the present, ghostly havoc breaks loose when Triss Bellamy takes a position managing a bookshop in that same building. As each hunt for answers, the doorway to the past threatens to close on any remaining hope"-- Provided by publisher.